Role of School Principal in Utilizing Student The LKPD to Improve Quality of Learning - Herlina Sumanti; Laili Komariyah; Masrur Masrur; Jamil Jamil; Sudarman Sudarman; Azainil Azainil (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2026)
Abstract: This study aims to plan, organized, implement, supervise, and evaluate the use of student the LKPD called LKPD by the school principal to improve the quality of learning at SMP Negeri 1 Samarinda. This research combines descriptive and qualitative methods, the descriptive method provides a comprehensive overview of the principal's management phenomena regarding the use of student the student worksheets (LKPD) without any manipulation or intervention, and qualitative methods approach through a case study using data collection techniques such as interviews, observations, and document analysis. The results of the study indicate the school principal carry out educational management functions systematically through planning, organizing, implementing and monitoring the use of the LKPD. The implementation of these management functions has helped to promote a higher quality of learning that is more active, contextual and learner-centre. The school principal management of the use of the the LKPD published by the Department of Education and Culture has been carried out in accordance with the POAC management functions (Planning, Organizing, Actuating, Controlling) and the school principal role as EMASLIM refers to concept of the school principal role as an educator, manager, administrator, supervisor, leader, innovator, and motivator—and has made a tangible contribution to improving the quality of the learning process. This study contributes to the field of educational management by demonstrating that the management of teaching materials by the school principal forms part of instructional leadership practices that influence the quality of learning. Keywords: The principal management, student worksheet, learning quality